Advancing the First World Ocean Assessment: Wider Caribbean Region Workshop; Miami, Florida, 13–15 November 2012. (9th April 2013) - Tirpak, Elizabeth; Halpern, David
Abstract : World Ocean Assessment (WOA) regional workshops enlist expertise for the WOA Pool of Experts, update regional knowledge on the marine environment, and build capacity to conduct assessments and benefit from assessments. WOA was described in Eos ( 93 (50), 521, doi:10.1029/2012EO500001). For the Wider Caribbean Region (WCR) Workshop, the United States Mission to the United Nations (UN) invited all UN missions, in accordance with WOA guidelines. The WCR workshop attracted 94 people from 32 countries with a wide range of expertise, including ocean, fishery, and biodiversity sciences; living and nonliving resource management; and capacity building. Attendees represented academia, governments, industry, and nongovernmental organizations.